Indolent B-Cell Lymphomas Associated with HCV Infection: Clinical and Virological Features and Role of Antiviral Therapy - Luca Arcaini; Michele Merli; Stefano Volpetti; Sara Rattotti; Manuel Gotti; Francesco Zaja (Clinical and Developmental Immunology)
The association between hepatitis C virus (HCV) infection and B-cell non-Hodgkin’s lymphomas (NHL) has been demonstrated by epidemiological studies, in particular in highly endemic geographical areas such as Italy, Japan, and southern parts of United States. In these countries, together with diffuse large B-cell lymphomas, marginal zone lymphomas are the histotypes most frequently associated with HCV infection; in Italy around 20–30% cases of marginal zone lymphomas are HCV positive. Recently, antiviral treatment with interferon with or without ribavirin has been proved to be effective in the treatment of HCV-positive patients affected by indolent lymphoma, prevalently of marginal zone origin. An increasing number of experiences confirmed the validity of this approach in marginal zone lymphomas and in other indolent NHL subtypes like lymphoplasmacytic lymphoma. Across different studies, overall response rate was approximately 75%. Hematological responses resulted significantly associated with the eradication of the virus. This is the strongest evidence of a causative link between HCV and lymphomas. The aim of this paper is to illustrate the relationship between HCV infection and different subtypes of indolent B-cell lymphomas and to systematically summarize the data from the therapeutic studies that reported the use of antiviral treatment as hematological therapy in patients with HCV-associated indolent lymphomas.